The TALE homeodomain of PBX1 is involved in human primary testis‐determination. Issue 8 (21st May 2019) - Eozenou, Caroline; Bashamboo, Anu; Bignon‐Topalovic, Joelle; Merel, Tiphanie; Zwermann, Oliver; Lourenco, Diana; Lottmann, Henri; Lichtenauer, Urs; Rojo, Sandra; Beuschlein, Felix; McElreavey, Ken; Brauner, Raja
Abstract: Human sex‐determination is a poorly understood genetic process, where gonad development depends on a cell fate decision that occurs in a somatic cell to commit to Sertoli (male) or granulosa (female) cells. A lack of testis‐determination in the human results in 46, XY gonadal dysgenesis. A minority of these cases is explained by mutations in genes known to be involved in sex‐determination. Here, we identified a de novo missense mutation, p.Arg235Gln in the highly conserved TALE homeodomain of the transcription factor Pre‐B‐Cell Leukemia Transcription Factor 1 (PBX1) in a child with 46, XY gonadal dysgenesis and radiocubital synostosis. This mutation, within the nuclear localization signal of the protein, modifies the ability of the PBX1 protein to localize to the nucleus. The mutation abolishes the physical interaction of PBX1 with two proteins known to be involved in testis‐determination, CBX2 and EMX2. These results provide a mechanism whereby this mutation results specifically in the absence of testis‐determination. Abstract : We identified a de novo missense mutation in the highly conserved TALE homeodomain of PBX1 associated with 46, XY complete gonadal dysgenesis (CGD). The lack of testis‐determination in the child can be explained by the inability of the mutated protein to interact with two key proteins required for testis formation, CBX2 and EMX2.